Optimal Location Analysis for Tourist Accommodation Development in Jepara - Nida, Rizqita Shofa; Esariti, Landung; Damayanti, Maya (Department of Urban and Regional Planning, Universitas Diponegoro, 2023)
Tourist accommodations in Jepara Regency are focalized on only a number of strategic tourist locations. As such, their insufficient spread constrains tourist accessibility to necessities. This article analyzes and specify locations in Jepara Regency that may be developed into tourist accommodations such so that they are optimally distributed to boost and optimize tourism activities. The analysis carried out employed the weighted overlay quantitative research approach using Geographic Information System software. From the analysis, a map of recommendation was made containing the optimal locations in Jepara Regency to be developed into tourist accommodations consisted of the North, East, and West regions. The locations were determined in consideration of potential for visual beauty, accessibility, proximity to tourist attractions, accessibility to public facilities, proximity to city center, land use, and the slope of land. This study recommends that the government continues to mediate the development of accommodations so as not to be overly centered in the western part of Jepara and considers the regional capacity and environmental conditions of the area in the next few years. Furthermore, the government needs to strengthen the tourism systems in the northern and eastern regions so that these regions are prepped in time to be developed.Keywords: Accommodation, Tourism, Optimal Location